Implementasi Terapi Suwuk Pada Penderita Axiety Disorder di Pondok Pesantren Darur Rohman Kiemas - Maujuhan Syah, Ahmad (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
For Muslim communities, seeking treatment that refers to the treatment of the Prophet Muhammad SAW is an option. The Prophet has taught several methods of treatment for several diseases, there are at least three types, namely, first, using traditional medicines which are taken directly from nature. Second, treatment mixed with spiritual elements of Sufism (sufism), third, is a combination of the two previous methods, namely combining Sufistic treatment with the use of traditional medicines. The aim of this research is to determine the condition of students with anxiety disorders and understand the implementation of suwuk therapy at the Darur Rohman Kiemas Sendangagung Lamongan Islamic Boarding School. The method in this research is to use descriptive qualitative research methods with the subjects being students with anxiety disorders. Data collection uses observation, interviews and literature review. The results of the research were that the condition of students in the severe category received special treatment because students who were still in severe condition were not able to communicate with other students. The tendency of students with severe conditions is to get angry, destroy things, become hysterical, and hurt themselves and others. The application of suwuk therapy at the Darur Rohman Kiemas Islamic Boarding School is by using salt media. The treatment given is 1) repentance bath, 2) dhikr, and 3) giving suwuk salt.